Synthesis of new benzo[a]phenoxazinium probes possessing carboxylic ester, hydroxyl and amino functional groups: photophysical studies in dry ethanol and conjugation with CdTe quantum dots - Raju, B. Rama (2014)
A new series of benzo[a]phenoxazinium chlorides possessing hydroxyl, ethyl ester and amino functional groups as terminal substituents at the 9- and 5-positions of the tetracyclic aromatic system in different combinations, was synthesised. A photophysical study was carried out in anhydrous ethanol and water, as a function of solution pH. Acid dissociation constants were estimated and found to depend on the nature of the terminal groups. Experimental evidence for an additional molecular form is presented and is compatible with J-aggregates of the deprotonated form of some of the earlier studied the benzo[a]phenoxazinium chlorides. The benzo[a]phenoxazinium chloride possessing the amino terminal group was reacted with the carboxylic acid of CdTe quantum dots (QDs) to obtain a conjugate of the dye and QD. Initial photophysical characterisation indicates both photoinduced electron and energy transfer between the QD and the attached benzo[a]phenoxazinium chloride.